"Silence" as a strategy during a corporate crisis – the case of Volkswagen's "Dieselgate". Issue 4 (5th August 2019) - Stieglitz, Stefan; Mirbabaie, Milad; Kroll, Tobias; Marx, Julian
Abstract : Purpose: The purpose of this paper is to investigate the communication behaviour on Twitter during the rise of a preventable corporate crisis. It aims to contribute to situational crisis response strategies, and to broaden the authors' understanding of legitimacy management. In September 2015, Volkswagen's (VW) emission scandal became public and caused debates also in social media. By applying complementing tools of data analysis to the Twitter communication around the "Dieselgate" crisis, this study unfolds a field of tension between corporate strategy and public perception. Design/methodology/approach: The authors collected Twitter data and analysed approximately 2.1m tweets relevant to the VW crisis. The authors approached the data by separating the overall communication in peak and quiet phases; analysing the peaks with social network analysis techniques; studying sentiments and the differences in each phase; and specifically examining tweets from VW's corporate accounts with regard to the situational crisis communication theory (SCCT) and legitimacy. Findings: VW's very few tweets were not able to reduce the emotionality and sentiment of the ongoing Twitter discussion. Instead, even during quiet phases, the communication remained rather negative. The analysis suggests that VW followed a strategy not covered by SCCT, i.e. keeping silent. Practical implications: The discovered strategy of keeping silent extends the SCCT and is linked to legitimacy management. Learnings from this study help decision makers to put social media response strategies into practice to swiftly recover from crises or refrain from certain strategies to avoid further reputational damage. Social implications: Examining the underlying communication patterns of a crisis case with societal magnitude such as "Dieselgate" helps sensitising customers and executives to utilise social media channels more comprehensible in future crises. Originality/value: The study uncovers the unconventional and yet barely addressed crisis response strategy of a global enterprise while devising unique realisations for practitioners and communication researchers. It contributes to existing knowledge about situational crisis response strategies, and broadens the authors' understanding of legitimacy management in times of social media ubiquity.